Equatorial F-region irregularities generated by the Rayleigh-Taylor instability mechanism: rocket observations from Brazil - Muralikrishna,Polinaya (2007)
Several sounding rockets carrying plasma diagnostic experiments were launched from the Brazilian rocket launching stations in Natal (5.9ºS, 35.2ºW Geog. Lat.) and Alcântara (2.31ºS, 44.4ºW Geog. Lat.). Langmuir Probes (LP) were used to measure the height profiles of electron density and electron temperature and High Frequency Capacitance (HFC) probes were used to measure electron density. The LP's were also used to measure the amplitude of electron density fluctuations. A detailed study of the characteristic features of electron density irregularities in the scale size range of less than a meter to a few kilometres, observed by rocket-borne electron density probes under different ionospheric conditions is presented here. The main objective of these studies is the identification of these irregularities from the point of view of the dynamic and electrodynamic processes responsible for their generation. The existing theories of the Rayleigh Taylor Instability (RTI) mechanism applicable for conditions of the geomagnetic equatorial ionosphere over Brazil are critically examined in the light of the observations. The observed characteristics of the irregularities during four rocket launches are compared with the theoretically expected characteristics. These results confirm the operation of a cascade process that is responsible for the generation of a wide spectrum of irregularities. The large-scale irregularities are first generated probably by the RTI mechanism that creates conditions favourable for the operation of the Cross-Field (CFI) or the Gradient Drift Instability (GDI) mechanism. From the k-spectra of irregularities it is possible to obtain the spectral index n corresponding to the height chosen. In most of the cases the estimated spectral indices agree well with those published in the literature for the cases of irregularities generated by the GDI mechanism.